The interface of wildlife and nature tourism - Shively, Rachel (Kansas State University, 2023)
The relationship between tourism and wildlife is complex and multifaceted, with impacts on both the environment and human well-being. This dissertation will investigate the intersection of tourism and wildlife, focusing on three main aspects: the impact of outdoor recreation on wildlife, the potential of virtual nature tourism to decrease impacts on wildlife while still providing health benefits to participants, and the balance between access and protection for both humans and wildlife. This dissertation focuses on the relationship between wildlife tourism and its impact on both participants and wildlife. The author examines several factors that can shape the development of wildlife tourism, such as the format of the tourism, the beliefs and motivations of the participants, and the effects on both wildlife and participants. Virtual nature tourism will be explored as a potential solution to decrease the impact on sensitive wildlife while increasing access to learn about and observe wildlife in their natural habitat. This can include wildlife webcams and guided tours that can be viewed remotely, such as WildEarth safaris. Virtual nature tourism can be beneficial for people who cannot travel to experience nature in person due to time, financial, or health limitations, while still providing health benefits. The author notes that outdoor recreation tourism can have both health benefits for participants and negative impacts on wildlife. In order to balance these factors, the author suggests that understanding the patterns of wildlife behavior and human recreation is crucial in developing regulations and educational programs that ensure both wildlife and tourism can thrive. The author also explores the dynamics between wildlife and protected area tourists and how decisions made by park managers affect the balance between conservation and recreation. The author suggests that protected areas can benefit from a zoning approach that caters to different types of tourists and their preferences. Overall, the author argues that a better understanding of the relationship between wildlife tourism and its impact on both participants and wildlife is crucial for informed management decisions that benefit both. Documenting the variations in benefits and impacts on humans and wildlife will inform management decisions that will allow for a range of access and protection. This dissertation aims to contribute to the larger debate and ongoing efforts towards a sustainable balance between tourism and wildlife conservation.
Keywords: Human dimensions; Wildlife; Nature tourism; Virtual tourism; Outdoor recreation; Protected areas